Characterization of the Key Flavor Compounds and Metabolic Pathways in Sichuan Sun Vinegar Using a Flavor-Oriented Approach - WANG Chuan, ZHAO Yulin, LIU Jun, LI Li, LIAO Yuting, CAO Rong (Shipin Kexue)
This study analyzed the unique flavor characteristics and formation mechanism of Sichuan sun vinegar. A comparative analysis of the flavor components in Sichuan sun vinegar and other vinegars was performed using high-performance liquid chromatography (HPLC) and headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS). The results revealed that five amino acids and three organic acids were the predominant flavor components in Sichuan sun vinegar at the solid-state fermentation phase and 22 volatile flavor substances were detected at this stage. Metagenomic sequencing identified 14 microbial genera involved in the formation of flavor compounds in Sichuan sun vinegar, including Lactobacillus, Brettanomyces, Lichtheimia, Acetobacter, and Pichia. Notably, Lactobacillus and Lichtheimia were identified to play pivotal roles in the degradation of substrates such as starch, cellulose, and arabinoxylan. Furthermore, the biosynthesis of characteristic flavor compounds, such as acetaldehyde, 4-ethyl-2-methoxyphenol, and 2-methoxy-4-methylphenol, was closely associated with the metabolic activities of Lactobacillus, Acetobacter, and Brettanomyces. Using a “bottom-up” approach, we successfully identified the core microorganisms responsible for the formation of characteristic flavor substances in Sichuan sun vinegar and elucidated the relationship between these microorganisms and the formation of flavor substances as well as their metabolic mechanisms. These findings not only provide a robust scientific foundation for understanding the flavor formation process of Sichuan sun vinegar, but also offer significant theoretical insights and practical guidance for enhancing the flavor quality of Sichuan sun vinegar.